Internal migration and housing costs—A panel analysis for Germany. Issue 4 (23rd November 2020) - Stawarz, Nico; Sander, Nikola; Sulak, Harun
Abstract: The emergent crisis of affordable urban housing coupled with a sustained decline in internal migration rates in many Western countries warrants a thorough exploration of the relation between housing costs and internal migration. Although it is well established that housing is an important contextual determinant of migration flows, little attention has thus far been paid to the ways in which rising housing costs shape internal migration. In this paper, we use a time‐series of annual intercounty migration in Germany for the period 2004–2017 to examine the association between increasing housing prices and changes in internal migration flows. For this, we apply fixed effects Poisson panel regression models to migration flow tables. Our results show that regions with rising housing costs experience declining inflows. In larger cities, rising housing costs are also associated with increasing outflows. Our study provides new insights into the relationship between house price dynamics and internal migration.